Ética de la investigación en modelos animales de enfermedades humanas - Rodríguez Yunta, Eduardo (Acta Bioethica, 2007)
This paper argues about the ethical implications of using animals as models for human medicine development. This reflection adopts an intermediate stand between the extreme positions of condemning all research with animal considering it irrelevant, and that of exaggerating and promoting research with animals as models for human diseases. Our stand considers that in the current scientific state, reseach with animals is necessary for adjusting to the moral imperative of curing and preventing human diseases, but methods for replacing and reducing the number of animals as well as diminishing their suffering must be sought.